Surface and interface microstructural properties of Ru thin films grown on InSb (111) substrates at room temperature - Kim, TW; Lee, DU; Lee, JH; Yoon, YS; Lee, JY; Park, HL (ELSEVIER, 2000)
Ru thin films were grown on p-InSb (111) substrates by the ion-beam-assisted deposition method with the goal of producing a new kind of Ru/InSb heterostructures with high-quality heterointerfaces. Atomic force microscopy (AFM) and X-ray diffraction (XRD) measurements showed that the Ru films grown on InSb substrates at room temperature were polycrystalline thin layers with very smooth surfaces. Auger electron spectroscopy (AES) and Rutherford backscattering measurements (RBS) showed that the composition of the as-grown film was Ru and that the Ru/InSb heterointerface had relatively sharp interfaces. Transmission electron microscopy (TEM) and selected area electron-diffraction measurements showed that the grown Ru film was a polycrystalline layer with small grain size. These results indicate that the Ru layer grown on p-InSb (111) can be used for stable contacts and metal electrodes with low resistivities in electronic devices such as metal-semiconductor field-effect-transistors and memory capacitor between electrodes based on InSb substrates. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: SCANNING TUNNELING MICROSCOPY; GAAS(110); TRANSPORT; CLUSTERS; STATES